Mesenchymal Stromal Cell-Derived Extracellular Vesicles as Biological Carriers for Drug Delivery in Cancer Therapy - Sanmartin, María Cecilia; Borzone, Francisco Raúl; Giorello, María Belén; Yannarelli, Gustavo; Chasseing, Norma Alejandra (Frontiers in Bioengineering and Biotechnology, 2022)
Cancer is the second leading cause of death worldwide, with 10.0 million cancer deaths in 2020. Despite advances in targeted therapies, some pharmacological drawbacks associated with anticancer chemo and immunotherapeutic agents include high toxicities, low bioavailability, and drug resistance. In recent years, extracellular vesicles emerged as a new promising platform for drug delivery, with the advantage of their inherent biocompatibility and specific targeting compared to artificial nanocarriers, such as liposomes. Particularly, mesenchymal stem/stromal cells were proposed as a source of extracellular vesicles for cancer therapy because of their intrinsic properties: high in vitro self-renewal and proliferation, regenerative and immunomodulatory capacities, and secretion of extracellular vesicles that mediate most of their paracrine functions. Moreover, extracellular vesicles are static and safer in comparison with mesenchymal stem/stromal cells, which can undergo genetic/epigenetic or phenotypic changes after their administration to patients. In this review, we summarize currently reported information regarding mesenchymal stem/stromal cells-derived extracellular vesicles, their proper isolation and purification techniques - from either naive or engineered mesenchymal stem/stromal cells - for their application in cancer therapy, as well as available downstream modification methods to improve their therapeutic properties. Additionally, we discuss the challenges associated with extracellular vesicles for cancer therapy, and we review some preclinical and clinical data available in the literature.